Adaptive fuzzy control method of hydrogen fuel cell gas supply system. Issue 1 (July 2021) - Wang, Weidong; Chen, Jing; Xiao, Chun; Cheng, Nanding
Abstract: This paper takes the hydrogen fuel cell gas supply system as the research object. Firstly, it analyzes the working principle of the hydrogen fuel cell and the control requirements of the gas supply system, then uses the fuzzy adaptive PID control algorithm to regulate the gas pressure of the system. Finally, Matlab/Simulink software simulation platform is used for simulation verification, and the control effects of conventional PID control and fuzzy adaptive PID control are compared. The results show that the gas supply system based on fuzzy adaptive PID control can effectively regulate the gas pressure value and has a good control effect.